Harbouring Dissent: Greek Independent and Social Media and the Antifascist Movement - Croeser, Sky; Highfield, T. (Fibreculture Publications, 2016)
This article examines Greek activists’ use of a range of communication technologies, including social media, blogs, citizen journalism sites, Web radio, and anonymous networks. Drawing on Anna Tsing’s theoretical model, the article examines key frictions around digital technologies that emerged within a case study of the antifascist movement in Athens, focusing on the period around the 2013 shutdown of Athens Indymedia. Drawing on interviews with activists and analysis of online communications, including issue networks and social media activity, we find that the antifascist movement itself is created and recreated through a process of productive friction, as different groups and individuals with varying ideologies and experiences work together.